Konsekuensi dari Halal Brand Equity pada Restoran Halal Cepat Saji di Indonesia - Natasya Desti Wulandari (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research is to find out how halal brand image, customer satisfaction, trust, and loyalty affect halal brand value among halal restaurant customers. This study utilized 220 respondents. Purposive sampling is the sampling method used. Structural Equation Model (SEM) method was used to analyze the data. The researcher found that (1) halal brand image has a positive effect on halal brand satisfaction, (2) halal brand image has a positive effect on halal brand trust, (3) halal brand image has no positive effect on halal brand equity, (4) halal brand satisfaction has no positive effect on halal brand equity, (5) halal brand trust has a positive effect on halal brand loyalty, (6) halal brand loyalty has a positive effect on halal brand equity.